Acupuncture Treatment for Social Defeat Stress - Kawanokuchi, Jun; Takagi, Ken; Tanahashi, Nobuyuki; Yamamoto, Teruhisa; Nagaoka, Nobuyuki; Ishida, Torao; Ma, Ning (Frontiers in Behavioral Neuroscience, 2021)
Depression is a mood disorder characterized by disordered affect, thoughts, cognition, and behavior. Antidepressant therapy is often the primary treatment for depression. However, antidepressant therapy may cause unwanted side effects, and its effects are slow. Therefore, some patients are seeking alternative treatments for depression, such as acupuncture. However, there are many unclear points regarding the mechanism of the effect of acupuncture on depression. In recent years, we have reported that acupuncture improves the symptoms of mild depression induced by water-immersion stress in a rat model and depression induced by forced swimming in a mouse model. In this study, we examined the effect of acupuncture on the symptoms of social defeat stress (SDS)-induced depression in mice that most closely resemble human symptoms. In this study, we investigated the preventive and therapeutic effects of acupuncture as part of GV20 “Bai-Hui” and Ex-HN3 “Yintang” on model mice with depression induced by SDS. To examine the mechanism of the preventive and therapeutic effects of acupuncture on depression model mice, we examined the expression of neurotrophic factors in the brains of SDS mice. Two weeks of simultaneous acupuncture stimulation as part of GV20 and Ex-HN3 restored SDS-reduced brain-derived neurotrophic factor (BDNF), neurotrophin (NT)-3, and NT-4/5 expression, which was not observed with antidepressants. In contrast, acupuncture stimulation suppressed nerve growth factor (NGF) expression induced by SDS. These results suggest that acupuncture treatment could be effective in correcting the imbalance in the expression of neurotrophic factors. Furthermore, the effects of acupuncture on the expression of neurotrophic factors appear earlier than those of antidepressants, suggesting that it may be a useful treatment for depression.